2007
DOI: 10.30843/nzpp.2007.60.4610
|View full text |Cite
|
Sign up to set email alerts
|

Combination of two odour chemical lures does not increase thrips capture in field bioassays

Abstract: Used in isolation several odour chemicals are known to increase trap capture of some thrips especially flowerinhabiting species This study examined the combined use of two structurally distinct odour chemicals both known to increase thrips trap capture in isolation Field bioassays using water traps were undertaken at two sites in New Zealand to target different thrips species Water traps had (1) no odour (water) (2) panisaldehyde only (3) methyl isonicotinate only (4) panisaldehyde and methyl isonicotinate mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…The results of the UK trials corroborated previous studies that showed application of Lurem-TR™ increases mean sticky trap catches of F. occidentalis (Teulon et al , 2007 ; Broughton and Harrison, 2012 ; Muvea et al ., 2014 ; Teulon et al, 2014 ; Broughton et al ., 2015 ). The (S) -(−)-verbenone treatments significantly increased trap catches at all concentrations, demonstrating the sensitivity of F. occidentalis to the compound, as previously demonstrated by electrophysiological and behavioural laboratory based assays (Abdullah et al , 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…The results of the UK trials corroborated previous studies that showed application of Lurem-TR™ increases mean sticky trap catches of F. occidentalis (Teulon et al , 2007 ; Broughton and Harrison, 2012 ; Muvea et al ., 2014 ; Teulon et al, 2014 ; Broughton et al ., 2015 ). The (S) -(−)-verbenone treatments significantly increased trap catches at all concentrations, demonstrating the sensitivity of F. occidentalis to the compound, as previously demonstrated by electrophysiological and behavioural laboratory based assays (Abdullah et al , 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…Blending two or more attractive compounds to increase their attractiveness would seem an obvious step towards trap efficiency improvement. However, blends of two structurally distinct attractants, panisaldehyde and methyl isonicotinate did not result in a higher number of T. tabaci caught compared to catches in traps baited with either compound alone [52]. The authors of the study suggested that T. tabaci has only one odour receptor that reacts to both chemicals used in this trial.…”
Section: Using Attractants For Thrips Trappingmentioning
confidence: 71%
“…The thrips lure in yellow sticky traps (20.63) was found highly significant over the yellow sticky traps (0.81) against thrips as p value is less than 0.05 (Table 4). Teulon et al (2007) for T. tabaci the mixtures of para-anisaldehyde and methyl isonicotinate proved to be only as strong as the most powerful lure for the thrips. The whitefly lure was not found to be significant against the yellow sticky traps.…”
Section: Resultsmentioning
confidence: 92%